2015
DOI: 10.1158/1538-7445.am2015-3852
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3852: Prevalent loss of BRCA1 and BRCA2 expression in African TNBC suggests their prominent role in sporadic carcinogenesis

Abstract: BRCAness is a property shared by breast tumors with sporadic BRCA1 mutations or arising in patients with germline BRCA1 mutations, or tumors which down-regulate BRCA1 expression by other mechanisms. Women with African ancestry have been shown to have breast tumors that have characteristics similar to BRCA mutated tumors, but there is scant data on the signaling and regulation of the BRCA1 and BRCA 2 pathways in theses tumors. We have hypothesized that defective expression of key players in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The frequency of p53 expression in TNBC cases is like the prevalence rate reported in Ghana (31.0%) by Ameh-Mensah et al [28] but lower than the frequency rate reported in Morocco (41.0%) by Jouli et al [29]. Here, the frequency of BRCA2 loss in TNBC is higher than the prevalence rate reported by Jiagge et al [30] and Xie et al [31] in Ghana (40%) and China (20%), respectively. The difference in BRCA2 expression in TNBC could be race and lifestyle-related.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The frequency of p53 expression in TNBC cases is like the prevalence rate reported in Ghana (31.0%) by Ameh-Mensah et al [28] but lower than the frequency rate reported in Morocco (41.0%) by Jouli et al [29]. Here, the frequency of BRCA2 loss in TNBC is higher than the prevalence rate reported by Jiagge et al [30] and Xie et al [31] in Ghana (40%) and China (20%), respectively. The difference in BRCA2 expression in TNBC could be race and lifestyle-related.…”
Section: Discussionsupporting
confidence: 50%
“…Here, the frequency of BRCA2 loss in TNBC is higher than the prevalence rate reported by Jiagge et al . [30] and Xie et al . [31] in Ghana (40%) and China (20%), respectively.…”
Section: Discussionmentioning
confidence: 99%